2021
DOI: 10.3389/fmolb.2021.687760
|View full text |Cite
|
Sign up to set email alerts
|

m6A-Related lncRNAs Are Potential Biomarkers for the Prognosis of Metastatic Skin Cutaneous Melanoma

Abstract: Background: The incidence of skin cutaneous melanoma (SKCM) has risen more rapidly than any other solid tumor in the past few decades. The median survival for metastatic melanoma is only six to nine months and the 5°years survival rate of patients with conventional therapy is less than 5%. Our aim was to reveal the potential molecular mechanism in m6A modification of lncRNA and provide candidate prognostic biomarkers for metastatic SKCM.Methods: lncRNAs expression level was obtained by re-annotation in TCGA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…As for the prognosis of SKCM, we solely selected the mRNA levels of the protein-coding PRGs to establish the prognostic model. Although there were still some gaps with some models based on other genes, the results suggested that PRGs had an effective prognostic performance in SKCM (56). In addition to transcriptome data that can be used for these analyses, we hypothesize that other omics data, such as proteome and metabolome, can be used similarly for tumor diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As for the prognosis of SKCM, we solely selected the mRNA levels of the protein-coding PRGs to establish the prognostic model. Although there were still some gaps with some models based on other genes, the results suggested that PRGs had an effective prognostic performance in SKCM (56). In addition to transcriptome data that can be used for these analyses, we hypothesize that other omics data, such as proteome and metabolome, can be used similarly for tumor diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…In decades, there have been many studies on data mining and modeling based on gene expression profiles and clinical outcomes of melanoma patients, which can provide reliable models for the diagnosis and prognosis of melanoma (55)(56)(57)(58). Compared with these studies, we used candidate genes to establish diagnostic and prognostic models in one study, which proved that PRGs were significantly valuable for the diagnosis and prognosis of SKCM.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Huang et al identified several m6A-related lncRNAs, which can act as potential prognostic markers of metastatic skin cutaneous melanoma. 19 However, the expression pattern of m6A-related lncRNAs in GC and its correlation with the immune microenvironment and effectiveness of immunotherapy remain unclear, warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of N6 adenosine is the most common RNA modification in eukaryotes, which can affect the occurrence and development of cancers by modifying mRNA and lncRNA [ 20 , 21 ]. Several studies have reported that m6AlncRNAs can also be used as cancer prognostic markers [ 22 , 23 , 24 ]. Previous studies have shown that m6A genes regulate the development of NSCLC [ 25 , 26 , 27 ] and act as potential prognostic markers of NSCLC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%